Variation of mechanical parameters of engineering materials under tension due to cyclic deformation by torsion - KOWALEWSKI, Z. L.; SZYMCZAK, T. (Engineering Transactions, 2009)
The paper presents experimental results of investigations carried out under complex stress state on the 2024 aluminium alloy (used by aircraft industry) and P91 steel (used at power plants). Second-order effects associated with cyclic loadings enforced by the trapezoidal signals in the two mutually perpendicular directions are identified. It is shown, how the cyclic loading and its parameters (strain amplitude and frequency) influence the simultaneous monotonic loading in the direction perpendicular with respect to the cyclic one. Moreover, the paper presents an analysis of the selected mechanical properties variations on the basis of an initial yield locus evolution.